KAJIAN KELEMBAGAAN AGRIBISNIS DALAM MENDUKUNG PENGEMBANGAN SISTEM USAHA PERTANIAN BERBASIS AGROEKOSISTEM - IKIN SADIKIN; RITA NUR SUHAETI; KEDI SURADISTRA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Research on agricultural institution with agribusiness orientation has not yet been given muchattention. Yet, farmers obtain information on technology, market and processing techniquesthrough the existing institutional roles, either in forms of organization, norms or communityfigures. The effort to accelerate the flow of agricultural inputs, process of technology transfer,and other production factors is a collective activity depicted in institutional network in localagricultural activities. A participatory observation using Rapid Appraisal of AgricultureKnowledge Systems (RAAKS) methodology concludes that the present primordial institution ineach production segment process positive potential to develop and that shared objective isrecognized as the starting point to develop an institution. Moreover, size of organization,membership status and institutional orientation also play important roles in the development of aninstitution, minimum commercial size, and policy on managerial development.